Correlation between Nurse Altruism Attitudes and Levels of Workplace Violence in Nurses at the Agroindustrial Regional Hospital in Jember Regency - Dodi Wijaya; Shobrina Rifatul Ula; Kholid Rosyidi Muhammad Nur; Nurfika Asmaningrum (KHD-Production, 2024)
Nurses with an altruistic attitude should prioritize the patients' interests over their own and strive to care for the welfare of others. This significantly affects the level of workplace violence among nurses, where violence in the workplace is a prevalent issue in the nurses' work environment. This research aims to analyze the relationship between nurses' altruism and the level of workplace violence among nurses in hospitals in the agro-industrial area of Jember district. This study employs a quantitative correlational design with a cross-sectional approach. Sampling was conducted using purposive sampling, resulting in a sample of 178 nurses. Data collection involved an altruism scale questionnaire and a workplace violence questionnaire. The research utilizes the Kendall Tau-C test. The research results revealed that 84.8% of respondents exhibited a high level of altruism, and 64.6% of respondents displayed a low level of workplace violence. Both variables show a p-value of 0.008 (p-value < 0.05), indicating a relationship between nurses' altruism and the level of workplace violence. This study shows a negative correlation value of r = -0.159, indicating a weak correlation. The lower the nurses' altruism attitude, the higher the level of workplace violence among them. The nurses' altruism attitude significantly influences patient assessment; the better the patient assessment provided by nurses, the lower the occurrence of conflicts.